2022-RA-1300-ESGO Multicenter experience on Sentinel Node Mapping in vulvar melanoma evaluation of clinical impact. (20th October 2022) - Fragomeni, Simona Maria; Collarino, Angela; Fuoco, Valentina; Martinelli, Fabio; Pasciuto, Tina; Corrado, Giacomo; Raspagliesi, Francesco; Rufini, Vittoria; Maccauro, Marco; Scambia, Giovanni; Garganese, Giorgia
Abstract : Introduction/Background: Melanoma of the vulva is a rare disease, often burdened by a poor prognosis. It is essential to define the optimal treatment in early stage disease. This multicenter retrospective study investigates the role of preoperative lymphoscintigraphy and sentinel node biopsy (SNB) and the impact of SNB on loco-regional control and survival in vulvar melanoma patients with clinically negative nodes (cN0). Methodology: All women treated between July 2013 and March 2021 were evaluated. Inclusion criteria consisted in: (i) histologically proven vulvar invasive melanoma, (iii) a Breslow tumor thickness of 1–4 mm and (iii) cN0 at preoperative evaluation. Patients selected underwent a preoperative lymphoscintigraphy followed by SNB with or without inguinofemoral lymphadenectomy. DFS and OS were assessed by the Kaplan-Meier method. Results: Eighteen women were included for a total of 28 groins studied. Planar images showed 51 sentinel nodes (SNs) in the enrolled inguinal regions. SNs were identified in all cases. Metastatic SNs were found in 5 patients (27, 7%) for a total of 8 metastatic nodes in 7 groins (25%). Recurrent disease was diagnosed in 10 (55, 5%) patients at 3 to 30 months: 7 were SN-negative, among which no specific groin recurrence was observed; 3 were SN-positive, among which 2 patients died of disease after 26.2 and 33.8 months, respectively. The overall mortality rate was 0% for SN negative and 40% in SN positive patients. OS and DFS at 36 months were 62.5% and 19.2%, respectively. The median DFS was 18.0 months (95% CI, 10.3–30.0). Conclusion: Lymphoscintigraphy followed by sentinel lymph node biopsy in patients with vulvar melanoma is feasible and allows adequate assessment of the stage of disease. Negative SNB is associated with low risk of groin relapse and good survival rate. Further prospective multicenter studies are needed to evaluate the criteria for clinical application.